Creativity and Cognition in Extreme Environments: The Space Arts as a Case Study - Hays, Kathryn; Kubli, Cris; Malina, Roger (Frontiers in Psychology, 2020)
Humans, like all organisms, have evolved to survive in specific environments, while some elect or are forced to live and work in extreme environments. Understanding cognition as it relates to environmental conditions, we use 4E cognition as a framework to explore creativity in extreme environments. Our paper examines space arts as a case study through the history, present practices, and future possible arts in the context of humans beyond the Kármán boundary of the Earth’s atmosphere. We develop a proposed taxonomy of space arts, based on prior taxonomies, and provide specific exemplars of space art developed by artists in space or for use by astronauts in space. Using examples of space art since the birth of the space age, we discuss 1) how human survival in extreme environments requires investment in the space arts, driven by consideration of all biopsychosocial factors and 2) how new scientific and engineering discoveries could be consequences or examples of creative thinking driven by artists in the various types of space art. We conclude by discussing possible benefits of space art, future research applications, and advocate that all space actors, government or private, involve artists in all projects beyond the Kármán Boundary of the Earth’s atmosphere.